KAJIAN DURABILITAS CAMPURAN PERKERASAN ASPAL YANG TERENDAM AIR LAUT DAN AIR TAWAR - Mataram, I Nyoman Karnata; Thanaya, I Nyoman Arya; Welimince, Yemina (Jurnal Ilmiah Teknik Sipil; Vol 25 No 2 (2021): Jurnal Ilmiah Teknik Sipil, Vol. 25 No. 2, Juli 2021DO - 10.24843/JITS.2021.v25.i02.p05, 2023)
Roads in coastal areas can be inundated by sea water or fresh water at high tide or during the rainy season. This research was conducted to analyze the effect of sea water and fresh water on the durability of asphalt pavements, especially the AC-WC mixture. This research begins with testing the aggregate and the asphalt used, then the manufacture of the test object to determine the optimal asphalt content (KAO) then continues with the manufacture of the test object without immersion which is compared to the test results with immersion carried out for 24, 48, and 72 hours. The test results show that seawater is more destructive than fresh water, where the value of each test decreases with the length of the immersion duration. KAO obtained 6.75%; stability without immersion 2367.40 kg; for 24 hours, 48 ??hours, and 72 hours of immersion in seawater, the stability was obtained respectively 2226.48 kg, 2163.36 kg, 2088.76 kg; and stability in immersion in fresh water 2272.38 kg, 2186.31 kg, and 2157.62 kg. For Marshall Test the residue without immersion was 93.08%, for soaking in sea water for 24 hours, 48 ??hours, and 72 hours respectively, it was obtained 86.86%, 82.76%; and 74.73% and 89.14%, 86.33%, 84.13% in fresh water. For the Cantabro test, the value without immersion was obtained 1.37%, for soaking in seawater for 24 hours, 48 ??hours, and 72 hours, it was obtained 2.16%, 3.16%, 6.20%; and 1.73%, 2.59%, 3.25% in fresh water. For the Indirect Tensile Strength (ITS) test, the non-immersion value obtained was 251.09 kPa; for soaking in seawater for 24 hours, 48 ??hours, and 72 hours, it was obtained 195.85 kPa, 160.70 kPa, 115.50 kPa; and 236.02 kPa, 180.78 kPa, 155.67 kPa in fresh water